2011
DOI: 10.1186/1472-6750-11-115
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and functional characterization of a cotton ubiquitination-related promoter and 5'UTR that drives high levels of expression in root and flower tissues

Abstract: BackgroundCotton (Gossypium spp.) is an important crop worldwide that provides raw material to 40% of the textile fiber industry. Important traits have been studied aiming the development of genetically modified crops including resistance to insect and diseases, and tolerance to drought, cold and herbicide. Therefore, the characterization of promoters and regulatory regions is also important to achieve high gene expression and/or a specific expression pattern. Commonly, genes involved in ubiquitination pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“…The expression pattern of the GhPME-like1 , GhβGal-like1 and GhPL-like1 genes in cotton agrees in principal with the regulatory pattern of their promoters because lower activity was observed in vegetative tissues and much higher activity was observed in flower buds, inflorescences and open flowers. The pGhPME-like1 , pGhβGal-like1 and pGhPL-like1 cotton promoters were compared with the uceA1.7 cotton promoter previously described by Viana et al (2011), and they showed significantly higher activity in Arabidopsis reproductive organs (data not shown). Histochemical assays of 6-mm cotton flower buds that had been bombarded with the tissue-specific promoters p300_GhPME-like1 (a), p760_GhPME-like1 (b), p1618_GhPME-like1 (c), pGhβGal-like1 (d) or pGhPl-like1 (e).…”
Section: Discussionmentioning
confidence: 93%
“…The expression pattern of the GhPME-like1 , GhβGal-like1 and GhPL-like1 genes in cotton agrees in principal with the regulatory pattern of their promoters because lower activity was observed in vegetative tissues and much higher activity was observed in flower buds, inflorescences and open flowers. The pGhPME-like1 , pGhβGal-like1 and pGhPL-like1 cotton promoters were compared with the uceA1.7 cotton promoter previously described by Viana et al (2011), and they showed significantly higher activity in Arabidopsis reproductive organs (data not shown). Histochemical assays of 6-mm cotton flower buds that had been bombarded with the tissue-specific promoters p300_GhPME-like1 (a), p760_GhPME-like1 (b), p1618_GhPME-like1 (c), pGhβGal-like1 (d) or pGhPl-like1 (e).…”
Section: Discussionmentioning
confidence: 93%
“…and the exact position of the structural domain needs to be verified by additional experiments. Previous studies reported that 5´-UTR could act as an enhancer in the gene expression process (Viana et al 2011;Kamo et al 2012;Kanoria and Burma 2012;Agarwal et al 2014). In absence of 5´-UTR region, MH (-1057 to -266) had a weaker GUS activity than MH10, which implies that 5´-UTR may regulate the MdHB-1 gene expression.…”
Section: Discussionmentioning
confidence: 93%
“…It confers high transcription levels without requiring other upstream cis-elements, except for the TATA box. 33 Studies on the promoter function of the amorpha-4,11-diene synthase (ADS) gene in Artemisia annua 34 and the high-molecular-weight glutenin subunit (HMW-GS) gene in Triticum aestivum 35 demonstrated that the 5 ′ UTR Py-rich stretch elements were important factors in the enhancement of the expression of the ADS and HMW-GS genes. The mutation length of the 5 ′ UTR Py-rich stretch motif influences promoter activity of the tryptophan decarboxylase (tdc) gene in Catharanthus roseus.…”
Section: Discussionmentioning
confidence: 99%